Students' Difficulties in English Speaking Class of Grade Eight at SMP PGRI 5 Denpasar - Ni Kadek Suci Dharma Yanti; Putu Santi Oktarina; Ni Wayan Satri Adnyani (Educational Journal, 2026)
This study aimed to identify the types of difficulties experienced by eighth-grade students at SMP PGRI 5 Denpasar in speaking English and to analyse the factors that influence the difficulties experienced by eighth-grade students at SMP PGRI 5 Denpasar in speaking English. This study used descriptive qualitative method with a case study design. The research subjects consisted of one English teacher and 12 students of class VIII G selected through purposive sampling technique. Data were collected using three instruments, namely (1) an observation sheet based on Penny Ur (1996) four categories of speaking difficulties, (2) a speaking performance test based on Brown (2019) theory covering the rubric with five aspects of speaking, and (3) a semi-structured interview exploring linguistic factors based on Burns & Joyce (1997) and non-linguistic factors based on Krashen (1982) Affective Filter Hypothesis. The data were analyzed using an interactive qualitative data analysis model by Miles and Huberman (2014) through data reduction, data display, conclusion and verification. The findings of this research showed that students experienced difficulties across all speaking aspects, with fluency was the lowest achievement percentage (33.1%). Based on Penny Ur (1996) classification, inhibition was the most dominant difficulty experienced by all students (100%). In terms of contributing factors, vocabulary and grammar were the most dominant linguistic factors, while anxiety was the most dominant non-linguistic factor. In conclusion, students’ English speaking difficulties were influenced by the interaction between linguistic and non-linguistic factors, especially vocabulary limitations, grammar problems, and anxiety, which reinforced inhibition and significantly affected students’ fluency in speaking English. Therefore, teachers are suggested to create a supportive classroom environment, provide scaffolding, and use interactive activities to help students build confidence in speaking English. Future research is suggested to examine other types of students' speaking difficulties and the factors influencing those difficulties, using more diverse research instruments and involving a broader sample and research context.